A perspective of advances in optical methods for biological sample characterization - Avila, Remy; Morales-Narváez, Eden; Loza-Alvarez, Pablo (Frontiers in Photonics, 2026)
Recent advances in optical methods for biological sample characterization reflect a profound shift driven by the convergence of photonic innovation, computational intelligence, and increasing biological complexity. In this Perspective, we present a concise overview and a forward-looking vision of five core domains that structure this Research Topic: advanced bioimaging technologies, next-generation optical biosensors, optical tweezers for nanoscale force measurements, particle tracking techniques, and artificial intelligence-driven data analysis. Rather than offering an exhaustive review, we highlight selected conceptual and technological developments, identify current limitations, and discuss emerging opportunities where integration across optical modalities and computational approaches may prove decisive. Particular emphasis is placed on multimodal and quantitative platforms, in situ and real-time measurements, high-throughput methodologies, and the growing role of physics-informed and on-the-fly artificial intelligence. By articulating common challenges and shared future directions across these five areas, this article aims to stimulate interdisciplinary dialogue, provide a unifying framework for the contributions collected in this Research Topic, and encourage further advances in optical technologies for probing complex biological systems.